Implementation of Aloe Vera for Wound Care in Post Op Amputation Patients with Diabetes Mellitus - Yuniar, Tarisa; Fitriani, Ade; Lismayanti, Lilis (Yayasan Inspirasi El Burhani, 2024)
Introduction: Diabetes mellitus is a chronic metabolic disease that can cause serious complications such as impaired wound healing. One of the severe complications is amputation, which requires optimal wound care to prevent infection and accelerate tissue regeneration. Aloe vera is known to have anti-inflammatory, antibacterial, and stimulating tissue regeneration effects. Objective: This study aims to implement the use of aloe vera gel in wound care in postoperative amputation patients with diabetes mellitus. Method: The study used a descriptive case study approach that focused on the nursing care process and the use of aloe vera gel as a nonpharmacological therapy in wound care. Result: After administering aloe vera gel for 3 meetings, the results showed that the wound looked more moist, increased hydration, sufficient exudate, and complete epithelialization without signs of infection. This intervention is effective in addressing skin/tissue integrity disorders. Conclusion: Aloe vera gel is proven to be effective in helping the wound healing process in postoperative amputation patients with diabetes mellitus and can be an alternative nursing implementation.